"Kriuknya Bikin Nagih, Kisahnya Bikin Penasaran" Perjalanan Penuh Motivasi dari Budidaya Central Jamur Tiram - Siti Aisyah; Ratna Sari Dewi; Santa Maria br Sibarani; Cantika Nurhaliza Hasibuan; Azhar Aditya (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
The Micro, Small, and Medium Enterprise (MSME) "Central Jamur Tiram" (Central Oyster Mushroom) in Medan, located at Jln. Mandala By Pass. Gg Orba No 31 Medan (Jln. Mandala By Pass. Gg Orba No 31 Medan), managed by Mr. Faisal, serves as a case study of successful business development in oyster mushroom cultivation. This research aims to explore Mr. Faisal's entrepreneurial journey, from business initiation and the innovation of processed oyster mushroom products to marketing strategies through online and offline platforms that led to success. The research method employed is qualitative with a case study approach, utilizing in-depth interviews with Mr. Faisal and direct observation of the business operations. The research findings indicate that perseverance, product innovation (such as mushroom chips and shredded mushroom), the utilization of spent mushroom substrate (baglog), and the ability to build a partnership network (partner farmers, souvenir shops, suppliers) are key success factors for "Central Jamur Tiram." Furthermore, the adaptation to online platforms for marketing significantly expanded the market reach. This study provides insights into the potential of oyster mushroom cultivation as a sustainable business opportunity and its economic contribution to the local community. The implications of this research can serve as inspiration and guidance for prospective entrepreneurs in the MSME sector, particularly in developing oyster mushroom cultivation businesses.